2008
DOI: 10.1152/japplphysiol.90641.2008
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the performance of three generations of ActiGraph accelerometers

Abstract: Rothney MP, Apker GA, Song Y, Chen KY. Comparing the performance of three generations of ActiGraph accelerometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
4
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(161 citation statements)
references
References 24 publications
12
141
4
4
Order By: Relevance
“…Though different accelerometer models have demonstrated comparability in trials for moderate and vigorous physical activity counts, 47 there appear to be differences at lower intensity levels that have implications for sedentary behavior measures. 48,49 To inform analyses, the accelerometer models are being compared in small studies, and correction algorithms to adjust for accelerometer model as well as for the difference between the ActiGraph and Actical, are being developed. All countries employed a 60-second epoch for storing data.…”
Section: Objectively-assessed Activity (Preferred)mentioning
confidence: 99%
“…Though different accelerometer models have demonstrated comparability in trials for moderate and vigorous physical activity counts, 47 there appear to be differences at lower intensity levels that have implications for sedentary behavior measures. 48,49 To inform analyses, the accelerometer models are being compared in small studies, and correction algorithms to adjust for accelerometer model as well as for the difference between the ActiGraph and Actical, are being developed. All countries employed a 60-second epoch for storing data.…”
Section: Objectively-assessed Activity (Preferred)mentioning
confidence: 99%
“…Accelerometer Previous studies have found the ActiGraph to be reliable and valid (15,(23)(24)(25) . A recent study (26) showed that 1 d of accelerometer data is adequate for estimating weekly moderate-to-vigorous PA (MVPA) in a representative US sample aged 20-85 years but we adopted a more stringent criterion because we aimed to examine hourly PA patterns.…”
Section: Measurementsmentioning
confidence: 99%
“…Second, data processing differs across devices Chen & Bassett, 2005), which is especially problematic in combination with the first problem. Accordingly, different devices produce significantly different numbers of counts for the exact same movements (Rothney, Apker, Song, & Chen, 2008). One possible reason for that is the so-called plateau phenomenon (cf.…”
mentioning
confidence: 99%